The Influence of Leadership on Employee Performance at PT. Marumo Indonesia Forging Karawang West Java - Dolfie Walla, Denny (CV. Publikasi Indonesia, 2023)
This research aims to determine the influence of leadership on employee performance at PT. Marumo Indonesia Forging Karawang, West Java, with a research focus on examining the determining factors of leadership in an organization or business. The type of research used is quantitative research, which is designed as a way of researching to obtain relevant data and information as a basis. The data sources used in this research are primary and secondary data sources with a total of 60 respondents. Data collection techniques using observation and distributing questionnaires. Data were analyzed using simple partial linear regression analysis. The results of this research show that there is a positive influence and there is significance between leadership variables and employee performance at PT. Marumo Indonesia Forging Karawang West Java obtained the results of a simple partial linear regression test which had the greatest influence on variable Y, especially variable so it can be concluded that there is a significant and positive influence of the Leadership variable (X) on employee performance (Y).